Beyond shareholder value? Why firms voluntarily disclose support for Black Lives Matter - CHEN, A. J. (Institutional Knowledge at Singapore Management University, 2021)
We investigate why firms voluntarily disclose support for the Black Lives Matter movement (BLM firms) even though these disclosures have little impact on shareholder value. We examine two competing explanations: that managers are acting in the interests of a broad set of stakeholders, or that they are engaging in “woke-washing.” Our evidence supports the stakeholder perspective since we find that BLM firms have more inclusive cultures on multiple dimensions – from their board members, to employees, to the rights of shareholders, and to the compensation structure of top executives. Furthermore, BLM firms face less risk in speaking out since they are part of stakeholder networks that are more supportive of BLM. BLM firms have competitors that spoke out, share directors with other firms that spoke out, and are headquartered in communities that supported BLM. We develop an “inclusivity index” that classifies 68 percent of BLM firms as “authentic” and 18 percent as “woke-washing.” Out of sample tests verify that the inclusivity index is useful for predicting which firms speak out on other social causes.